Switching to daratumumab SC from IV is safe and preferred by patients with multiple myeloma - Mateos, Maria-Victoria; Rigaudeau, Sophie; Basu, Supratik; Spicka, Ivan; Schots, Rik; Wrobel, Tomasz; Cook, Gordon; Beksac, Meral; Gries, Katharine S; Kudva, Anupa; Tromp, Brenda; Van Rampelbergh, Rian; et al. (Journal of oncology pharmacy practice, 2023)
INTRODUCTION: Two phase 3 studies demonstrated superior efficacy of intravenous daratumumab (DARA IV) plus bortezomib/melphalan/prednisone (ALCYONE) or lenalidomide/dexamethasone (Rd; MAIA) versus standard-of-care regimens for transplant-ineligible newly diagnosed multiple myeloma. In these studies, patients could switch from DARA IV to subcutaneous daratumumab (DARA SC) while receiving daratumumab monotherapy in ALCYONE (as of Cycle 11) or daratumumab plus Rd in MAIA. The phase 3 COLUMBA study demonstrated noninferiority of DARA SC to DARA IV. DARA SC reduced administration time, allowing patients to spend less time in healthcare settings, a relevant practical consideration for patient care in the COVID-19 pandemic/settings of limited healthcare resources. METHODS: DARA SC 1800 mg was administered every 4 weeks, per approved dosing schedules. We evaluated safety and patient-reported experience (ALCYONE only) among patients who switched from DARA IV to DARA SC. RESULTS: Fifty-seven patients in ALCYONE and 135 in MAIA switched to DARA SC. Three (2.2%; MAIA) patients reported injection-site reactions, all of which were mild. No infusion-related reactions occurred with DARA SC. In ALCYONE, >80% of patients preferred DARA SC over DARA IV. Grade 3/4 treatment-emergent adverse events (TEAEs) occurred in 5.3% of patients in ALCYONE and 25.9% in MAIA; one (0.7%; MAIA) patient experienced a TEAE with an outcome of death. CONCLUSION: For transplant-ineligible newly diagnosed multiple myeloma, DARA SC (monotherapy/with Rd) was safe and preferred over DARA IV. ClinicalTrials.gov, NCT02195479/NCT02252172.
Keywords: Bortezomib; protokoly protinádorové kombinované chemoterapie; pandemie; bortezomib; daratumumab; Multiple myeloma; transplant-ineligible; lidé; Multiple Myeloma; mnohočetný myelom; intravenous; Pandemics; COVID-19; subcutaneous; Antineoplastic Combined Chemotherapy Protocols; Humans